Geomorphic and forest cover controls on flooding: central Nepal Himalaya - Marston, Richard A.; Kleinman, Jack; Miller, Maynard (My University, 1996)
Devastating monsoon season floods in the central Nepal Himalaya have been difficult to predict with any precision, reliability, or accuracy. Deforestation is often blamed as the principal cause of flooding. This paper uses field data at 22 stream crossings, together with drainage basin morphometric data and forest cover data, to determine the dominant controls on bank-full discharge from monsoon storms. Results demonstrate that 82 percent of the variation in bank-full discharge can be explained as a function of drainage area alone; forest cover did not add explanatory power. Findings from this study can be used to guide planning for future projects that will be affected by flood hazards in the central Nepal Himalaya, including irrigation, hydropower, and footbridge construction.
Keywords: Deforestation; Floods; Himalayas; Nepal